A high voltage fast charging lithium ion battery and electrolyte

By using gel polymer electrolytes and nano-inorganic fillers in the electrolytes of lithium-ion batteries, a stable physical interface is formed, and the problem of unstable electrolytes under high voltage and fast charging conditions is solved, achieving higher battery performance and safety.

CN118136945BActive Publication Date: 2025-03-18JIANGXI DINTEL BATTERY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410467154.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2025-03-18
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

The existing electrolyte system for lithium-ion batteries cannot be effectively compatible under high voltage and fast charging conditions, resulting in problems such as unstable electrolyte, uneven interface reaction, and poor thermal stability.

Method used

Gel polymer electrolyte is used as the base electrolyte, and nano-inorganic fillers, such as boehmite and alumina complex, are added to it to form a stable physical interface, inhibiting the oxidative decomposition of polymer electrolytes and liquid solvents, while improving the mechanical and thermal stability of the electrolyte.

Benefits of technology

The stable operation of electrolytes within a wider voltage range is achieved, the fast charging performance and cycle stability of lithium-ion batteries are improved, the formation of lithium dendrites is avoided, and the safety and performance of the battery is ensured.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary battery materials. More specifically, it relates to a high-voltage fast-charging lithium-ion battery and electrolyte. The products provided by the present invention include a base solvent, a lithium salt, a functional additive, a polymer electrolyte, and a nano-inorganic filler; wherein the base solvent is dispersed in the polymer electrolyte to form a gel polymer electrolyte; the lithium salt, the functional additive, and the nano-inorganic filler are dispersed in the gel polymer electrolyte; the polymer electrolyte is selected from polyethylene oxide; the nano-inorganic filler is compounded by boehmite and alumina in a mass ratio of 8:1-10:1. The base solvent is prepared from the following raw materials in parts by weight: 50-60 parts of ethylene carbonate, 10-15 parts of fluorinated ethylene carbonate, 8-10 parts of acrylonitrile, and 3-5 parts of methyl ethylene oxide; the functional additives include film-forming protection additive vinyl sulfate, overcharge protection additive DTD, and flame retardant additive trimethyl phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery materials, and more specifically, relates to a high-voltage fast-charge lithium-ion battery and an electrolyte. Background Art

[0002] Under high voltage conditions, the electrolyte of lithium batteries may face a variety of failure problems, which are mainly related to the chemical stability of the electrolyte, interface reaction and the performance of additives. The following are some common failure problems:

[0003] 1. Oxidative decomposition of the solvent: Under high voltage conditions, the solvent molecules in the electrolyte may undergo an oxidation reaction on the surface of the positive electrode, causing the solvent to decompose and form unstable decomposition products. This decomposition consumes lithium ions in the electrolyte, reducing the number of available lithium ions in the battery, thereby reducing the battery's capacity and cycle life.

[0004] 2. Formation of unstable solid electrolyte interface (SEI): On the surface of the negative electrode, especially the lithium metal negative electrode, the electrolyte may participate in the formation of the SEI layer. If the SEI layer is formed unevenly or unstable, it may lead to an increase in the interfacial impedance during the battery cycle, affecting the battery's charge and discharge efficiency and cycle stability.

[0005] 3. Thermal stability of the electrolyte: High-voltage electrolytes may be more susceptible to thermal decomposition and gas generation at high temperatures (high temperatures generated by rapid battery charging), which may cause battery expansion, leakage, and even safety accidents.

[0006] 4. Failure of electrolyte additives: In order to improve the performance of the electrolyte, some functional additives are usually added. Under high voltage conditions, these additives may fail and cannot effectively inhibit the decomposition of the electrolyte or stabilize the electrode interface.

[0007] 5. Structural changes in positive electrode materials: Under high voltage, positive electrode materials may undergo structural changes, such as phase change, release of lattice oxygen, etc. These changes may destroy the structural stability of the positive electrode materials and affect the stability of the electrolyte.

[0008] 6. Compatibility issues between electrolyte and electrode materials: High voltage electrolyte needs to have good compatibility with electrode materials. If the electrolyte and electrode materials undergo an undesirable chemical reaction, it may cause battery performance to deteriorate.

[0009] To address these problems, researchers are developing new high-voltage electrolyte systems, such as using new solvents, improving additives, designing more stable SEI / CEI interfaces, and other strategies to improve the stability of the electrolyte under high voltage conditions and the overall performance of the battery. Summary of the invention

[0010] The technical problem to be solved by the present invention is to overcome the problem that the existing electrolyte system for lithium-ion batteries is not effectively compatible when facing higher voltage windows and fast charging conditions, and provide a high-voltage fast-charging lithium-ion battery and electrolyte.

[0011] The object of the present invention is to provide an electrolyte for a high-voltage fast-charge lithium-ion battery.

[0012] Another object of the present invention is to provide a high voltage fast charging lithium ion battery.

[0013] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0014] An electrolyte for a high-voltage fast-charge lithium-ion battery, comprising a basic solvent, a lithium salt, a functional additive, a polymer electrolyte, and a nano-inorganic filler;

[0015] Wherein, the base solvent is dispersed in the polymer electrolyte to form a gel polymer electrolyte;

[0016] The lithium salt, the functional additive, and the nano inorganic filler are dispersed in the gel polymer electrolyte;

[0017] The polymer electrolyte is selected from polyethylene oxide;

[0018] The nano inorganic filler includes boehmite.

[0019] The above scheme uses a gel polymer electrolyte as the basic electrolyte in high-voltage usage scenarios, and adds nano-inorganic fillers thereto. The added nano-inorganic fillers can form a stable physical interface between the lithium salt in the electrolyte and the network skeleton of the polymer electrolyte, thereby effectively inhibiting the oxidative decomposition of the polymer electrolyte and the liquid solvent dispersed therein under high voltage conditions, thereby allowing the electrolyte to work normally in a wider voltage range; in addition, by using boehmite as an inorganic filler, it can be combined with polyethylene oxide to construct an electrolyte skeleton with excellent liquid retention capacity, and the electrolyte skeleton benefits from the addition of boehmite, and its mechanical stability and thermal stability are significantly improved, so that the overall shape of the gel electrolyte is stable and reliable under high voltage or fast charging conditions. In addition, boehmite is often used in the surface coating of lithium battery separators, and the physical interface formed on the surface of polyethylene oxide can also enhance the wettability of liquid solvents to polyethylene oxide, thereby improving the overall lithium ion transmission capacity of the product and effectively ensuring the fast charging performance of the product.

[0020] Furthermore, the base solvent is prepared from the following raw materials in parts by weight: 50-60 parts of ethylene carbonate, 10-15 parts of fluorinated ethylene carbonate, 8-10 parts of acrylonitrile, and 3-5 parts of methyl ethylene oxide.

[0021] Furthermore, the functional additives include film-forming protection additive vinyl sulfate, overcharge protection additive DTD, and flame retardant additive trimethyl phosphate; wherein the mass ratio between the vinyl sulfate, the DTD and the trimethyl phosphate is 4:1:3; and the amount of the functional additives is 8-10% of the mass of the solvent.

[0022] Furthermore, the nano inorganic filler is compounded by boehmite and alumina in a mass ratio of 8:1-10:1.

[0023] Furthermore, in the nano inorganic filler, the D50 of the boehmite is 60-80 nm; and the D50 of the alumina is 0.3-0.4 times that of the boehmite.

[0024] Furthermore, the added amount of the nano inorganic filler is 6-8% of the mass of the polymer electrolyte.

[0025] The above technical solution selects a mixed filler system of boehmite and alumina and controls the particle size and addition amount of the two. The two cooperate in regulating the transmission behavior of lithium ions in the gel electrolyte, making the transmission of lithium ions more uniform, effectively avoiding the formation of lithium dendrites during fast charging, and effectively improving the fast charging performance of lithium battery products.

[0026] Furthermore, the lithium salt is selected from any one or a combination of two of LiPF6, LiTFSI, and LiDFOB; and the concentration of the lithium salt in the lithium-ion battery electrolyte is 1.2-1.4 mol / L.

[0027] A high-voltage fast-charge lithium-ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte for a lithium-ion battery according to any one of claims 1 to 7;

[0028] Wherein, the diaphragm is composed of a base film and a PVDF adhesive layer sprayed on the surface of the base film, the PVDF adhesive layer is coated on both surfaces of the base film at the same time, and the base film is a porous PP or PE film;

[0029] The electrolyte for lithium-ion batteries is distributed on two surfaces of the separator and is respectively attached to the positive electrode and the negative electrode.

[0030] Furthermore, the thickness of the base film is 5-6 μm, the single layer thickness of the PVDF adhesive layer is 2.0-2.5 μm, and the single layer thickness of the lithium ion battery electrolyte is 8-12 μm.

[0031] Furthermore, the thickness of the electrolyte for lithium-ion batteries on the positive electrode side is 8-9 μm, and the thickness of the electrolyte for lithium-ion batteries on the negative electrode side is 10-12 μm.

[0032] The above scheme further arranges electrolyte layers of different thicknesses on both sides of the base membrane. Specifically, the electrolyte layer on the positive electrode side is relatively thin, while the electrolyte layer on the negative electrode side is relatively thick. The advantage of this is that during the fast charging process, lithium ions are released from the positive electrode material and embedded in the negative electrode material. At this time, the rate at which lithium ions are released from the positive electrode is significantly higher than the rate at which they are embedded in the negative electrode. This is why the bottleneck of conventional fast charging capacity is often at the negative electrode. The inventors have explored and found that for the gel electrolyte used in the present invention, when the positive electrode side is relatively thin, the probability of being oxidized on the positive electrode side can be reduced when the voltage increases. A thicker electrolyte layer is arranged on the negative electrode side, which can provide better lithium ion storage capacity and avoid lithium precipitation caused by the accumulation of lithium ions on the negative electrode surface. DETAILED DESCRIPTION

[0033] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0034] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0035] Example 1

[0036] Preparation of electrolyte for lithium-ion batteries:

[0037] Polyethylene oxide and N-methylpyrrolidone (NMP) are mixed in a mass ratio of 1:8 and poured into a container, and stirred and mixed with a stirrer at a speed of 400 r / min, and then heated under stirring to completely dissolve the polyethylene oxide to obtain a polyethylene oxide solution; for example, the lithium ion battery is a 4.5V lithium ion battery.

[0038] After the polyethylene oxide solution is cooled to room temperature, the nano inorganic filler is continuously added to the container containing the polyethylene oxide solution under stirring, and then ultrasonic dispersion is performed for 45 minutes at an ultrasonic frequency of 65 kHz to obtain a dispersion;

[0039] The dispersion is poured into a flat mold, cast and coated, and then vacuum dried to remove NMP to obtain an electrolyte membrane; lithium salt is added to the base solvent at a concentration of 1.2 mol / L, and then a functional additive of 8% by mass of the base solvent is added, and then stirred and mixed with a stirrer at a speed of 600 r / min for 4 hours to obtain an electrolyte;

[0040] The obtained electrolyte membrane is immersed in an electrolyte solution so that the electrolyte membrane absorbs the obtained electrolyte solution, and the electrolyte is taken out after continuous immersion for 8 hours at room temperature to obtain an electrolyte for a lithium ion battery;

[0041] The nano inorganic filler is prepared by compounding boehmite and alumina in a mass ratio of 8:1.

[0042] In the nano inorganic filler, the D50 of the boehmite is 60nm; the D50 of the alumina is 0.3 times that of the boehmite;

[0043] The addition amount of the nano inorganic filler is 6% of the mass of the polymer electrolyte (polyethylene oxide);

[0044] The base solvent is prepared from the following raw materials in parts by weight: 50 parts of ethylene carbonate, 10 parts of fluorinated ethylene carbonate, 8 parts of acrylonitrile, and 3 parts of methyl ethylene oxide;

[0045] The functional additives include film-forming protective additive vinyl sulfate, overcharge protective additive DTD, and flame retardant additive trimethyl phosphate; wherein the mass ratio of the vinyl sulfate, the DTD, and the trimethyl phosphate is 4:1:3;

[0046] The lithium salt is selected from LiPF6;

[0047] Lithium-ion battery composition:

[0048] Select NCM as the positive electrode active material, Ni:Co:Mn=5:3:2; select artificial graphite as the negative electrode active material;

[0049] The diaphragm is composed of a base film and a PVDF adhesive layer sprayed on the surface of the base film, wherein the PVDF adhesive layer is simultaneously coated on both surfaces of the base film, and the base film is a porous PP film;

[0050] The thickness of the base film is 5 μm, and the single layer thickness of the PVDF adhesive layer is 2.0 μm;

[0051] The electrolyte for lithium-ion batteries is distributed on the two surfaces of the separator and is respectively attached to the positive electrode and the negative electrode; the thickness of the electrolyte for lithium-ion batteries on the positive electrode side is 8 μm, and the thickness of the electrolyte for lithium-ion batteries on the negative electrode side is 10 μm.

[0052] Example 2

[0053] Preparation of electrolyte for lithium-ion batteries:

[0054] Pour polyethylene oxide and N-methylpyrrolidone (NMP) into a container at a mass ratio of 1:9, stir and mix with a stirrer at a speed of 500 r / min, and then heat under stirring to completely dissolve the polyethylene oxide to obtain a polyethylene oxide solution;

[0055] After the polyethylene oxide solution is cooled to room temperature, the nano inorganic filler is continuously added to the container containing the polyethylene oxide solution under stirring, and then ultrasonic dispersion is performed for 50 minutes at an ultrasonic frequency of 70 kHz to obtain a dispersion;

[0056] The dispersion is poured into a flat mold, cast and coated, and then vacuum dried to remove NMP to obtain an electrolyte membrane; lithium salt is added to the base solvent at a concentration of 1.3 mol / L, and then a functional additive is added at 9% of the base solvent mass, and then stirred and mixed with a stirrer at a speed of 700 r / min for 5 hours to obtain an electrolyte;

[0057] The electrolyte membrane is immersed in an electrolyte solution, so that the electrolyte membrane absorbs the electrolyte solution, and the electrolyte is taken out after continuous immersion for 10 hours at room temperature to obtain an electrolyte for a lithium ion battery;

[0058] The nano inorganic filler is prepared by compounding boehmite and alumina in a mass ratio of 9:1;

[0059] In the nano inorganic filler, the D50 of the boehmite is 70nm; the D50 of the alumina is 0.35 times that of the boehmite;

[0060] The addition amount of the nano inorganic filler is 7% of the mass of the polymer electrolyte (polyethylene oxide);

[0061] The base solvent is prepared from the following raw materials in parts by weight: 55 parts of ethylene carbonate, 12 parts of fluorinated ethylene carbonate, 9 parts of acrylonitrile, and 4 parts of methyl ethylene oxide;

[0062] The functional additives include film-forming protective additive vinyl sulfate, overcharge protective additive DTD, and flame retardant additive trimethyl phosphate; wherein the mass ratio of the vinyl sulfate, the DTD, and the trimethyl phosphate is 4:1:3;

[0063] The lithium salt is selected from LiTFSI;

[0064] Lithium-ion battery composition:

[0065] Select NCM as the positive electrode active material, Ni:Co:Mn=5:3:2; select artificial graphite as the negative electrode active material;

[0066] The diaphragm is composed of a base film and a PVDF adhesive layer sprayed on the surface of the base film, wherein the PVDF adhesive layer is simultaneously coated on both surfaces of the base film, and the base film is a porous PE film;

[0067] The thickness of the base film is 5.5 μm, and the single layer thickness of the PVDF adhesive layer is 2.2 μm;

[0068] The electrolyte for lithium-ion batteries is distributed on the two surfaces of the separator and is respectively attached to the positive electrode and the negative electrode; the thickness of the electrolyte for lithium-ion batteries on the positive electrode side is 8.5 μm, and the thickness of the electrolyte for lithium-ion batteries on the negative electrode side is 11 μm.

[0069] Example 3

[0070] Preparation of electrolyte for lithium-ion batteries:

[0071] Pour polyethylene oxide and N-methylpyrrolidone (NMP) into a container at a mass ratio of 1:10, stir and mix with a stirrer at a speed of 600 r / min, and then heat under stirring to completely dissolve the polyethylene oxide to obtain a polyethylene oxide solution;

[0072] After the polyethylene oxide solution is cooled to room temperature, the nano inorganic filler is continuously added to the container containing the polyethylene oxide solution under stirring, and then ultrasonic dispersion is performed for 60 minutes at an ultrasonic frequency of 75 kHz to obtain a dispersion;

[0073] The dispersion is poured into a flat mold, cast and coated, and then vacuum dried to remove NMP to obtain an electrolyte membrane; lithium salt is added to a base solvent at a concentration of 1.4 mol / L, and then a functional additive of 10% by mass of the base solvent is added, and then stirred and mixed with a stirrer at a speed of 800 r / min for 6 hours to obtain an electrolyte;

[0074] The obtained electrolyte membrane is immersed in an electrolyte solution so that the electrolyte membrane absorbs the obtained electrolyte solution, and the electrolyte is taken out after continuous immersion for 12 hours at room temperature to obtain an electrolyte for a lithium ion battery;

[0075] The nano inorganic filler is prepared by compounding boehmite and alumina in a mass ratio of 10:1.

[0076] In the nano inorganic filler, the D50 of the boehmite is 80 nm; the D50 of the alumina is 0.4 times that of the boehmite;

[0077] The addition amount of the nano inorganic filler is 8% of the mass of the polymer electrolyte (polyethylene oxide);

[0078] The base solvent is prepared from the following raw materials in parts by weight: 60 parts of ethylene carbonate, 15 parts of fluorinated ethylene carbonate, 10 parts of acrylonitrile, and 5 parts of methyl ethylene oxide;

[0079] The functional additives include film-forming protective additive vinyl sulfate, overcharge protective additive DTD, and flame retardant additive trimethyl phosphate; wherein the mass ratio of the vinyl sulfate, the DTD, and the trimethyl phosphate is 4:1:3;

[0080] The lithium salt is selected from LiDFOB;

[0081] Lithium-ion battery composition:

[0082] Select NCM as the positive electrode active material, Ni:Co:Mn=5:3:2; select artificial graphite as the negative electrode active material;

[0083] The diaphragm is composed of a base film and a PVDF adhesive layer sprayed on the surface of the base film, wherein the PVDF adhesive layer is simultaneously coated on both surfaces of the base film, and the base film is a porous PP film;

[0084] The thickness of the base film is 6 μm, and the single layer thickness of the PVDF adhesive layer is 2.5 μm;

[0085] The electrolyte for lithium-ion batteries is distributed on the two surfaces of the separator and is respectively attached to the positive electrode and the negative electrode; the thickness of the electrolyte for lithium-ion batteries on the positive electrode side is 9 μm, and the thickness of the electrolyte for lithium-ion batteries on the negative electrode side is 12 μm.

[0086] Example 4

[0087] The present embodiment differs from the embodiment 1 in that no alumina is added and the other conditions remain unchanged.

[0088] Example 5

[0089] The present embodiment is different from the embodiment 1 in that the D50 of the boehmite and the alumina are both 60 nm, and the other conditions remain unchanged.

[0090] Example 6

[0091] Compared with Example 1, the present embodiment is different in that: the electrolyte for lithium-ion batteries is distributed on the two surfaces of the diaphragm and is respectively attached to the positive electrode and the negative electrode; the thickness of the electrolyte for lithium-ion batteries on the positive electrode side is 10 μm, and the thickness of the electrolyte for lithium-ion batteries on the negative electrode side is 8 μm, and the other conditions remain unchanged.

[0092] Example 7

[0093] Compared with Example 1, the present embodiment is different in that: the electrolyte for lithium-ion batteries is distributed on the two surfaces of the diaphragm and is respectively attached to the positive electrode and the negative electrode; the thickness of the electrolyte for lithium-ion batteries on the positive electrode side is 8 μm, and the thickness of the electrolyte for lithium-ion batteries on the negative electrode side is 8 μm, and the other conditions remain unchanged.

[0094] Comparative Example 1

[0095] The difference between this comparative example and Example 1 is that no nano inorganic filler is added, and other conditions remain unchanged.

[0096] The performance tests were performed on the products obtained in Examples 1-7 and Comparative Example 1. The specific test methods and test results are as follows:

[0097] Cycle performance test:

[0098] According to the formula of the above-mentioned embodiment or comparative example, a lithium ion battery is prepared into a soft-pack battery with a capacity of 5Ah in a glove box;

[0099] At 25°C, after the battery was fixed to capacity, it was charged at a rate of 0.33C and discharged at a rate of 0.5C, and a full charge and discharge cycle test was performed until the capacity of the battery decayed to 80% of the initial capacity. Then, the charge and discharge were stopped and the number of cycles was recorded. The specific test results are shown in Table 1.

[0100] Among them, during the full charging process, first use a constant current charging at a charging rate of 0.33C. After reaching the cut-off voltage (), continue to charge at a constant voltage until the current is lower than 0.025C, then stop charging and it is considered fully charged; during the full discharge process, use a discharge rate of 0.5C to discharge to a cut-off voltage of 2.8V, and then let it stand for 30 minutes.

[0101] Table 1: Cyclic performance test results

[0102] Cycle number / circle Example 1 1250 Example 2 1262 Example 3 1259 Example 4 1180 Example 5 1192 Example 6 1221 Example 7 1215 Comparative Example 1 950

[0103] It can be seen from the test results in Table 1 that the product obtained by the present invention can still maintain relatively excellent cycle performance under high voltage use.

[0104] High rate charging performance test:

[0105] According to the formula of the above-mentioned embodiment or comparative example, a lithium ion battery is prepared into a soft-pack battery with a capacity of 5Ah in a glove box;

[0106] At 25°C, after the battery is fixed in capacity, it is charged at a rate of 3C and discharged at a rate of 1C, and a full charge and discharge cycle test is performed until the capacity of the battery decays to 80% of the initial capacity. Then, the charge and discharge are stopped and the number of cycles is recorded. The specific test results are shown in Table 2.

[0107] Among them, during the full charging process, first use a constant current charging at a charging rate of 3C. After reaching the cut-off voltage (), continue to charge at a constant voltage until the current is lower than 0.025C, then stop charging and it is considered fully charged; during the full discharge process, discharge at a discharge rate of 1C until the cut-off voltage is 2.8V, and then let it stand for 30 minutes.

[0108] Table 2: High rate charging performance test results

[0109] Cycle number / circle Example 1 860 Example 2 869 Example 3 855 Example 4 822 Example 5 828 Example 6 832 Example 7 819 Comparative Example 1 550

[0110] It can be seen from the test results in Table 2 that the product obtained by the present invention can still maintain relatively excellent cycle performance when charged and discharged at a high rate.

[0111] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An electrolyte for a high voltage fast-charge lithium-ion battery, characterized in that: Including basic solvents, lithium salts, functional additives, polymer electrolytes, and nano inorganic fillers; The base solvent is dispersed in the polymer electrolyte to form a gel polymer electrolyte; the base solvent is prepared from the following raw materials in parts by weight: 50-60 parts of ethylene carbonate, 10-15 parts of fluorinated ethylene carbonate, 8-10 parts of acrylonitrile, and 3-5 parts of methyl ethylene oxide; The lithium salt, the functional additive, and the nano inorganic filler are dispersed in the gel polymer electrolyte; The polymer electrolyte is selected from polyethylene oxide; The nano inorganic filler is compounded with boehmite and alumina in a mass ratio of 8:1-10:1; the functional additives include film-forming protection additive vinyl sulfate, overcharge protection additive DTD, and flame retardant additive trimethyl phosphate; wherein the mass ratio between the vinyl sulfate, the DTD and the trimethyl phosphate is 4:1:3; the dosage of the functional additives is 8-10% of the mass of the solvent; among the nano inorganic fillers, the D50 of the boehmite is 60-80nm; the D50 of the alumina is 0.3-0.4 times that of the boehmite; the addition amount of the nano inorganic filler is 6-8% of the mass of the polymer electrolyte.

2. The electrolyte for high voltage fast charging lithium ion battery according to claim 1, characterized in that: The lithium salt is selected from any one of LiPF6, LiTFSI, and LiDFOB or a combination of two thereof; and in the lithium-ion battery electrolyte, the concentration of the lithium salt is 1.2-1.4 mol / L.

3. A high voltage fast charging lithium ion battery, characterized in that: A lithium-ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte according to any one of claims 1 to 2; The diaphragm is composed of a base film and a PVDF adhesive layer sprayed on the surface of the base film, the PVDF adhesive layer is coated on both surfaces of the base film at the same time, and the base film is a porous PP or PE film; The electrolyte for lithium-ion batteries is distributed on two surfaces of the separator and is respectively attached to the positive electrode and the negative electrode.

4. The high voltage fast-charge lithium-ion battery according to claim 3, characterized in that: The thickness of the base film is 5-6 μm, the single layer thickness of the PVDF adhesive layer is 2.0-2.5 μm, and the single layer thickness of the electrolyte for lithium ion batteries is 8-12 μm.

5. The high voltage fast-charge lithium-ion battery according to claim 4, characterized in that: The thickness of the electrolyte for lithium ion batteries on the positive electrode side is 8-9 μm, and the thickness of the electrolyte for lithium ion batteries on the negative electrode side is 10-12 μm.

Citation Information

Patent Citations

  • Gel polymer electrolyte with high lithium ion transference number and ionic conductivity and preparation method thereof

    CN115172872A